The Influence Of Local Revenue On Personnel Expenditure In The City Of Bengkulu - Sari, Mayang Sekar; Wagini, Wagini; Rahman, Abdul (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The purpose of this study was to determine the effect of Local Revenue (PAD) on employee spending in Bengkulu Province. The sample in this study was 10 cities and regencies in Bengkulu Province. The data collection method is documentation for PAD data and employee spending for the period 2019 to 2023. The data analysis method used is simple regression analysis, determination test and t-hypothesis test. The results of multiple linear regression testing obtained the regression equation Y = 250,608.568 + 1.649X with a positive regression direction, meaning that the higher the PAD, the higher the employee spending. Local Revenue (PAD) has a significant effect on employee spending because the significant value of 0.000 is smaller than 0.05. This means that the higher the PAD, the higher the employee spending. The determination coefficient of 0.711 means that the PAD variable is able to influence employee spending by 71.1%, while the remaining 28.9% is explained by other factors outside the independent variables used in this study.